MATHEMATICAL MODELING OF HEAT-EXCHANGE PROCESS IN CHAMBER HEATING FURNACE - V. I. Timoshpolskij; I. A. Trusova; D. V. Mendelev; P. E. Ratnikov (Литьë и металлургия, 2009)
The mathematical model of heat exchange in chamber heating furnace is developed and solved